PENGATUR KECEPATAN MOTOR DC SATU KUADRAN DENGAN METODE FEEDBACK IxR - Effendi; Muhammad Agil Haikal (J-Innovation, 2015)
To control the speed rotation of DC motor in single quadran as expected can be done by controlling SCRtrigger angle that connected with the armartur, the trigger angle can be generated by using LM324 as opampand comparator. The changes of current (I) on armartur winding to be reference for DC Motor speedrotation. The value of armature current for further used as feedback that connected with resistor (R)which has a very low resistance so that it can generate voltage (IxR) which represents the motor speedrotation. If the motor speed rotation different from speed reference then system will makes adjustments bychanging the trigger angle of SCR so that the motor speed rotation constant.